Social Determinants of Mental Health among Migrants, Refugees, and Displaced Populations: A Systematic Literature Review - Dudiyanto Pakaya; Fitryne Lihawa; Iswan Dunggio (Westscience Press, 2026)
Mental health among migrants, refugees, asylum seekers, and internally displaced persons has become an increasingly important public health concern, yet the evidence remains fragmented across population groups, determinants, and disciplinary traditions. This study aimed to systematically review the social determinants of mental health among migrants, refugees, and displaced populations, with particular attention to how employment, housing, social networks, and legal and policy conditions shape psychological outcomes across different migration contexts. This article was conducted as a Systematic Literature Review using a PRISMA aligned approach. The review drew on peer reviewed empirical studies identified through a structured Scopus based search strategy, supported by explicit inclusion and exclusion criteria, staged screening, design appropriate quality appraisal, and thematic synthesis. The review focused on adult migrants, refugees, asylum seekers, temporary migrant workers, and internally displaced persons, and examined mental health outcomes including depression, anxiety, distress, trauma related symptoms, wellbeing, and psychosocial functioning. The findings show that migrant mental health is shaped not only by trauma exposure but by interconnected post migration social determinants. Employment insecurity, underemployment, wage exploitation, and income instability were consistently associated with anxiety, depression, and psychological distress. Housing insecurity, overcrowding, poor living environments, and unstable shelter conditions emerged as major stressors affecting safety, autonomy, and future stability. Social support, family contact, and community ties functioned as important protective factors, but family separation, loneliness, and remittance obligations also generated emotional and financial strain. Legal precarity, exclusionary welfare systems, temporary visa regimes, and barriers to healthcare intensified structural vulnerability and restricted access to protection and care. Across the reviewed studies, these determinants operated cumulatively and interactively rather than independently, reinforcing the importance of multi level explanatory frameworks. Overall, the review demonstrates that mental health among migrants and displaced populations is best understood as a structural public health issue. The study contributes to existing knowledge by integrating fragmented evidence into a coherent framework linking material, relational, and policy determinants. It also highlights the need for longitudinal, comparative, and more inclusive research to support rights based and multisectoral policy responses.